Women and Romance The Consolations of Gender in the English Novel - Langbauer, Laurie (Cornell University Press, 2018)
According to Laurie Langbauer, the notion of romance is vague precisely because it represents the chaotic negative space outside the novel that determines its form. Addressing questions of form, Langbauer reads novels that explore the interplay between the novel and romance: works by Charlotte Lennox, Mary Wollstonecraft, Charles Dickens, George Eliot, and George Meredith. She considers key issues in feminist debate, in particular the relations of feminist to the poststructuralist theories of Lacan, Derrida, and Foucault. In highlighting questions of gender in this way, Women and Romance contributes to a major debate between skeptical and materialist points of view among poststructuralist critics.